Small business finance in Italy - Luigi Guiso (EIB Papers, 2003)
Using survey data on Italian manufacturing firms, this paper examines firms' capital structure and their access to financial debt, notably bank loans. We find that the share of financial debt in total liabilities is, on average, smaller for small firms than for large ones. However, this is not because the typical small firm borrows less than a large firm, but because small firms are more likely not to borrow at all. For firms that do borrow, the share of financial debt varies little with firm size. The absence of financial debt on the balance sheet of many firms is mainly because they do not want to borrow, not because lenders do not want to lend. Thus, credit rationing does not appear to be a widespread phenomenon, but when it happens, lack of size and equity seems to play a key role.
Keywords: 330; Klein- und Mittelunternehmen; Unternehmensfinanzierung; Italien